Probing Wnt pathway and functional signal in equine melanocytic neoplasms through quantitative proteomics and immunohistochemistry - Parichart Tesena; Ruethaiwan Vinijkumthorn; Amornthep Kingkaw; Petchpailin Yanyongsirikarn; Khajornpol Phasuk; Sekkarin Ploypetch; Narumon Phaonakrop; Sittiruk Roytrakul; Wanwipa Vongsangnak; Nawarus Prapaiwan (BMC Veterinary Research)
Abstract Background Equine melanocytic neoplasm (EMN) is a skin tumor commonly observed in grey horses. Limited research has yet to investigate proteomic profiles of EMN, particularly in the early stages and their expression patterns. This study, therefore, aimed to identify signature proteins from tissue biopsies to distinguish early EMN, severe EMN, and normal groups. Results Using proteomic analysis of 19 tissue samples (normal: n = 6, early EMN: n = 7, severe EMN: n = 6) through LC–MS/MS, 12,310 proteins were identified. Differentially expressed proteins (DEPs) and functional interaction analysis revealed significant overexpression of Wnt signature proteins, e.g., canonical (Wnt2B) and non-canonical (Wnt5B) Wnt signaling in early EMN stages. Immunohistochemical staining (IHC) towards immunolocalizing Wnt signature protein, particularly the Wnt2B functional signal, further verified its higher expression in early EMN compared to other groups. Conclusions These findings suggest that the Wnt pathway and functional insight are key mediators in signal transduction during early EMN, offering potential markers for initial stage detection. This study enhances the understanding of EMN mechanisms and the role of Wnt proteins, with implications for developing future diagnostic and therapeutic strategies.